Erratum: MURAT ÖZAYDINLI & CH. OLIVER COLEMAN (2012) Ampithoe bizseli n. sp. (Crustacea, Amphipoda) from the west coast of Turkey. Zootaxa, 3388, 17–28. - Özaydinli, Murat; Coleman, Ch. Oliver (Zootaxa, 2012)
(Erratum)